(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study examines the effect of slope exposure on the vertical distribution of carbonates and the development of alkalinity conditions in desalinated mountain brown soils of the Turkistan range. Soil samples collected from watershed, south-facing, and north-facing slopes were analyzed for carbonate (CO₂%) and pH values. The findings indicate that slope exposure significantly influences soil heat–moisture conditions, thereby affecting carbonate migration and alkalinity formation within the soil profile.